Advanced testing of systems-of-systems. - Homès, Bernard (Computer engineering series (London, England), 2022)
As a society today, we are so dependent on systems-of-systems that any malfunction has devastating consequences, both human and financial. Their technical design, functional complexity and numerous interfaces justify a significant investment in testing in order to limit anomalies and malfunctions. Based on more than 40 years of practice, this book goes beyond the simple testing of an application - already extensively covered by other authors - to focus on methodologies, techniques, continuous improvement processes, load estimates, metrics and reporting, which are illustrated by a case study. It also discusses several challenges for the near future. Pragmatic and clear, this book displays many examples and references that will help you improve the quality of your systemsof-systems efficiently and effectively and lead you to identify the impact of upstream decisions and their consequences. Advanced Testing of Systems-of-Systems 2 deals with the practical implementation and use of the techniques and methodologies proposed in the first volume.